2021
DOI: 10.5771/2192-4007-2021-3-326
|View full text |Cite
|
Sign up to set email alerts
|

It’s still a thing: digital inequalities and their evolution in the information society

Abstract: Internet diffusion has prompted research into differences in internet access, use and consequences. Exploiting the full potential of the ongoing digital transformation in all spheres of life-a proclaimed goal of governments and international organizations-requires ensuring equal opportunities and supporting disadvantaged individuals in their internet use. Using representative, population-level survey data from Switzerland spanning nearly a decade (2011-2019; Ntotal = 5,581), multiple multivariate regression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 32 publications
(43 reference statements)
0
8
1
Order By: Relevance
“…However, as the study’s primary aim was to learn about differences in normative influences on digital disconnection across generational groups, this limitation does not concern the study’s main aim (as it may have affected generations comparably). In this context, we also note that the study was conducted in Switzerland, which is characterized by high levels of digital media uptake with well over 90% of the population using the Internet (Festic et al, 2021). Thus, generalizations of the findings to regions with different digital infrastructures and cultures should be done with careful consideration.…”
Section: Discussionmentioning
confidence: 96%
“…However, as the study’s primary aim was to learn about differences in normative influences on digital disconnection across generational groups, this limitation does not concern the study’s main aim (as it may have affected generations comparably). In this context, we also note that the study was conducted in Switzerland, which is characterized by high levels of digital media uptake with well over 90% of the population using the Internet (Festic et al, 2021). Thus, generalizations of the findings to regions with different digital infrastructures and cultures should be done with careful consideration.…”
Section: Discussionmentioning
confidence: 96%
“…56 As a next step, research focusing on the measurement invariance of the WUS could highlight other factors of digital inequality, such as occupation and income, 2 and investigate whether the WUS is also invariant in cross-country settings. 30 Moreover, it may be interesting to test the convergent validity of the WUS with other survey measures of internet skills. In particular, this scale could be compared with those based on multidimensional measurement models to assess which theoretical dimensions of internet skills besides web-use skills are captured by the WUS.…”
Section: Limitations and Future Workmentioning
confidence: 99%
“…6,9,24,25 Indeed, there is a large difference between the lifestyles of those aged 50-64 years (largely employed) and those aged 65+ years (largely retired), leading to an increasing risk of social and digital exclusion in the older group. 21,[26][27][28] Differences in internet skills also relate to gender, with women reporting lower levels of internet skills 6,[29][30][31][32] and education; here, internet skills are shown to increase with level of education. 1,30,31…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, research on digital inequality has shown that individual factors influence Internet use (e.g., Festic et al 2021) and that these individual factors translate into different levels of socioeconomic status and socioeconomic inequalities (see Scheerder et al 2017). (Social) inequality measures related to the socioeconomic situation of individuals especially might suffer from nonresponse bias in online panels that underrepresent individuals with low IT literacy.…”
Section: Literature Overview and Research Questionsmentioning
confidence: 99%